COMMUNITY DEVELOPMENT DALAM PENANGGULANGAN KEMISKINAN - Sopandi, Andi (Fakultas Komunikasi, Sastra, dan Bahasa, 2011)
Community Empowerment program is often considered only as a slogan. The word is frequently used to attract general public attention. In fact, its implementation doesn?t consider basic principle of the implementation of Community Development, and even its usage is only to fulfill the requirement of development program. Therefore, efforts that need to be done to understand about the true essence and definition of community empowerment and Comdev basic principle as the main requirement, especially in countermeasure of poverty